Risk factors for excessive gestational weight gain in a UK population: a biopsychosocial model approach - S. M. Garay; L. A. Sumption; R. M. Pearson; R. M. John (BMC, 2021)
Abstract Background Gestational weight gain (GWG) can have implications for the health of both mother and child. However, the contributing factors remain unclear. Despite the advantages of using a biopsychosocial approach, this approach has not been applied to study GWG in the UK. This study aimed to investigate the risk factors of excessive GWG in a UK population, employing a biopsychosocial model. Methods This study utilised data from the longitudinal Grown in Wales (GiW) cohort, which recruited women in late pregnancy in South Wales. Specifically, data was collected from midwife recorded notes and an extensive questionnaire completed prior to an elective caesarean section (ELCS) delivery. GWG was categorised according to Institute of Medicine (IOM) guidelines. The analysis was undertaken for 275 participants. Results In this population 56.0% of women had excessive GWG. Increased prenatal depression symptoms (Exp(B)=1.10, p=.019) and an overweight (Exp(B)=4.16, p<.001) or obese (Exp(B)=4.20, p=.010) pre-pregnancy BMI, consuming alcohol in pregnancy (Exp(B)=.37, p=.005) and an income of less than £18,000 (Exp(B)=.24, p=.043) and £25-43,000 (Exp(B)=.25, p=.002) were associated with excessive GWG. Conclusion GWG is complex and influenced by a range of biopsychosocial factors, with the high prevalence of excessive weight gain in this population a cause for concern. Women in the UK may benefit from a revised approach toward GWG within the National Health Service (NHS), such as tracking weight gain throughout pregnancy. Additionally, this research provides evidence for potential targets for future interventions, and potentially at-risk populations to target, to improve GWG outcomes.